Pengenalan Fitur Free Pickup Service Pada Aplikasi “PosAja” Sebagai Upaya Mempermudah Masyarakat Dalam Mengirim Paket - Bagus Susanto; Fani Khoirotunnisa (Pakis Journal Institute, 2024)
Seeing the competition in the business market world is getting tighter, PT. Pos Indonesia (Persero) which provides goods or mail delivery services if it does not innovate it will be less competitive, currently PT. Pos Indonesia (Persero) is ranked number 3 nationally in the national ranking of services. Free pickup servive service or free package pick-up is an effort made by PT. Pos Indonesia (Persero) so that customers do not go to other delivery services. The PosAja Indonesia application has great potential with various services provided, but the concern of the Indonesian people for the PosAja application is still lacking because of a number of problems, including PosAja is still fairly new, so the author is very interested in introducing the application as a form of community service with the title